China Pakistan Economic Corridor Investment in Power Project and Emerging Narratives in Pakistan: A Political Economic Perspective - Noor Fatima; Kamran Riaz; Imran Ashraf, (ASIAN Journal of International Peace & Security (AJIPS), 2021)
Pakistan has been suffering from an energy deficit for over a decade, accounting for approximately 2% of the country's GDP. One of the major CPEC investments is in the energy sector, which accounts for 60% of the total investment and amounts to approximately US$35 billion in Pakistan's electric power sector, with the goal of increasing Pakistan's power production capacity. These projects are producing surpluses in power as according to the Pakistan Economic Survey 2019-20, the installed electricity generation capacity reached 37,402 MW in 2020, whereas Pakistan's total demand is nearly 25,000 MW. The surplus is due to 17 energy projects installed in various cities, which added 13000 MW to the National Grid Station. However, the CPEC investment in the energy sector has become a contentious issue, with many criticizing the project's political and economic management. How political economy influences state's decision making, undermining economic sector performance despite a lot of efficient projections. This paper will evaluate the influence of CPEC investments in power projects on Pakistan's power crises and will conclude with a political and economic perspective on the subject issue.